RANCANGAN SISTEM PENGERING IKAN BERBASIS IOT DENGAN PEMANAS ALTERNATIF - Setianingsih, Diah Patriana; Pasoloran, Moses (Foristek, 2025)
Fish drying is a technique in fish processing by reducing the water content in fish meat to inhibit the growth of microorganisms and extend the shelf life of the fish. Sunlight dependent, this process faces challenges in bad weather. This study develops a household scale IoT-based fish drying system with real-time temperature and humidity monitoring, utilizing incandescent and infrared lamps as alternative heat sources. It also evaluates the effectiveness of these heat sources in drying fish.The research was conducted in Balikpapan, focusing in Manggar Main Market area. The research methods included literature studies, observations, prototypes, and interviews with small business operators to select fish samples used in this study, namely tembang fish (Sardinella sp.) and scad (Decapterus spp.).The results show that infrared heaters reduce water content more effectively than incandescent lamp, which is around 66.7%, versus 57.1% for tembang fish and around 46.1% versus 38.4% for scad. The IoT-based monitoring system successfully displayed real time sensors measurement data on the website.The conclusion infrared heaters outperformed incandescent lamps in drying fish and the IoT-based monitoring system works effectively.